A gene catalogue of the Sprague-Dawley rat gut metagenome. Issue 5 (11th May 2018) - Pan, Hudan; Guo, Ruijin; Zhu, Jie; Wang, Qi; Ju, Yanmei; Xie, Ying; Zheng, Yanfang; Wang, Zhifeng; Li, Ting; Liu, Zhongqiu; Lu, Linlin; Li, Fei; et al.
Abstract: Background: Laboratory rats such as the Sprague-Dawley (SD) rats are an important model for biomedical studies in relation to human physiological or pathogenic processes. Here we report the first catalog of microbial genes in fecal samples from Sprague-Dawley rats. Findings: The catalog was established using 98 fecal samples from 49 SD rats, divided in 7 experimental groups, and collected at different time points 30 days apart. The established gene catalog comprises 5, 130, 167 non-redundant genes with an average length of 750 bp, among which 64.6% and 26.7% were annotated to phylum and genus levels, respectively. Functionally, 53.1%, 21.8%, and 31% of the genes could be annotated to KEGG orthologous groups, modules, and pathways, respectively. Conclusions: A comparison of rat gut metagenome catalogue with human or mouse revealed a higher pairwise overlap between rats and humans (2.47%) than between mice and humans (1.19%) at the gene level. Ninety-seven percent of the functional pathways in the human catalog were present in the rat catalogue, underscoring the potential use of rats for biomedical research.